PENGEMBANGAN OBJEK WISATA TAMAN KALONG DALAM MENINGKATKAN DAYA TARIK WISATAWAN DI KECAMATAN LALABATA KABUPATEN SOPPENG TAHUN 2010-2024 - Nurhimah, Nurhimah; Balkis, Syarifah; Rusdi, Rusdi (Universitas Negeri Makassar, 2024)
his research aims to find out: 1) Development of the Kalong Park tourist attraction in increasing tourist attraction in Lalabata District, Soppeng Regency. 2) Knowing the role of the government in increasing tourist attraction in Kalong Park, Lalabata District, Soppeng Regency. Descriptive qualitative research is the methodology employed. Three methods were utilized to collect data: documentation, interviews, and observation. Moreover, researchers employ the SWOT analysis approach as their analytical tool. The results of this research show 1.) The development of the Kalong Park tourist attraction in increasing tourist attraction in Lalabata District, Soppeng Regency is not independent of various factors that must be taken into account. These include internal factors, namely strengths and weaknesses, as well as external factors, namely opportunities and threats. The simple development model used was prepared by Lapier (1979) or often called Lapier tourism, which consists of 3 main components, namely the area of origin, the destination area and the area between. 2) Knowing the role of the government in increasing tourist attraction in Taman Kalong, Lalabata District, Soppeng Regency, managing tourism in general, namely providing infrastructure, expanding various forms of facilities, regulation and promotion to the general public.